Effects of LED Light Duration and Growing Media on Growth of Kale (Brassica oleracea var. Acephala) Microgreens - Hafizh Raihan; Susiyanti; Sulastri Isminingsih; Alfu Laila (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Kale (Brassica oleracea var. Acephala) is a plant that has good adaptability to various environmental conditions, and can be cultivated throughout the year with relatively simple cultivation. This study investigated the effects of LED light exposure duration (9, 12, and 15 hours/day) and various growing media (cocopeat, rice husk charcoal, and rockwool) on the growth of kale microgreens (Brassica oleracea var. Acephala) in a controlled indoor environment. Using a split-plot design, key parameters including plant height, leaf number, leaf greenness index, and fresh weight were evaluated over 14 days after planting (DAP). Results indicated that cocopeat significantly enhanced plant height (up to 10.76 cm) and fresh weight (0.55 g), while rockwool promoted superior leaf greenness (22.10 units) and leaf count (2.22 leaves). Longer light exposure (15 hours) improved leaf number, greenness, and fresh weight, with significant interactions observed in leaf count. These findings highlight optimal conditions for urban farming, supporting efficient nutrient-rich microgreen production amid declining agricultural land.